Overview of Guideline Recommendations for Screening and Management of Lung Cancer - Parry, Nicola (MD Conference Express, 2014)
This article discusses current recommendations for lung cancer screening, as well as some of the similarities and differences between the clinical practice guidelines of the European Society for Medical Oncology (ESMO), American Society of Clinical Oncology (ASCO), and National Comprehensive Cancer Network (NCCN) for treatment of lung cancer. This article also compares these guidelines for early-stage and locally advanced non—small cell lung cancer (NSCLC), demonstrating that despite their similarities, there are often subtle differences in their recommendations.